A Systematic Review on Social Cognition in ADHD: The Role of Language, Theory of Mind, and Executive Functions - Alessandra Capuozzo; Salvatore Rizzato; Giuseppe Grossi; Francesca Strappini (Brain Sciences)
Background: In this systematic review, conducted according to the PRISMA 2020 guidelines, we aimed to assess differences in the cognitive processes associated with social cognition—namely language, theory of mind (ToM), and executive functions (EFs)—between ADHD and control groups. Methods: The review included studies indexed in PubMed, Google Scholar, and PsycINFO up until May 2024. Eligible original peer-reviewed articles met the following criteria: they were written in English, included a clinical group with a current primary ADHD diagnosis, were empirical, included quantitative data, and utilized standardized and validated measures with adequate psychometric properties to assess social cognitive processes. Results and Discussion: A total of 1215 individuals with ADHD participated in the selected studies. Out of the 22 articles reviewed, 17 reported significant differences between ADHD and the controls across several cognitive processes related to language and EF rather than ToM. These processes included pragmatic skills, verbal and nonverbal communication, emotional prosody, interaction skills, sarcasm, paradoxical sarcasm recognition, ambiguous situations, emotion recognition, false belief, social problem solving, social behaviors, and gesture codification. We also discuss the limitations of the research and the implications of our findings. Systematic review registration: PROSPERO ID: CRD42023474681.